2018
DOI: 10.1186/s40008-018-0104-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the economic impact of South-to-North Water Diversion Project on industrial sectors in Beijing

Abstract: Beijing is a city with a shortage of water resources, and the water resource per capita is far below that of the lower limit of international water shortage. With rapid economic development and the improvement in living standards, the contradiction between the increasing demand for water and the shortage of water resources becomes increasingly pointed. It also becomes the main factor restricting the socioeconomic development of Beijing. Figure 1 shows the total water supply and structure of Beijing in 2008-201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…For example, Lin et al (2012) assessed the environmental benefit of the SNWTP and reported the total eco‐environmental benefits 38 billion RMB/year, while the eco‐economic benefit of delivered water in Hebei water‐recipient area was 5.526 billion RMB/year (Wang et al, 2018). For industrial sectors, the direct economic benefit generated by the SNWD to Beijing will be 38.72 billion RMB/year (Gao & Yu, 2018). Although there is a certain gap between our estimation and previous studies, there are in the same order of magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lin et al (2012) assessed the environmental benefit of the SNWTP and reported the total eco‐environmental benefits 38 billion RMB/year, while the eco‐economic benefit of delivered water in Hebei water‐recipient area was 5.526 billion RMB/year (Wang et al, 2018). For industrial sectors, the direct economic benefit generated by the SNWD to Beijing will be 38.72 billion RMB/year (Gao & Yu, 2018). Although there is a certain gap between our estimation and previous studies, there are in the same order of magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…The model coefficients A 0 , A 1 , A 2 , α i , β i , σ i are estimated from Equations ( 4), ( 6) and (8). The economic value of water for agricultural, industrial, and public water uses are estimated by isolating the marginal contribution of water to the total output value [10,36,37,39,45]. The marginal value can be obtained by the partial derivative of the production function with respect to water for three water use sectors following Equations ( 5), ( 7) and (9).…”
Section: Agricultural Industrial and Public Water Sectorsmentioning
confidence: 99%
“…It can lay the foundation for reaching a consensus on sharing the limited water supplies between different demand sectors to help achieve a balance between water supply and demand [29]. Regarding the evaluation of the economic value of different water sectors, existing research has focused more on how to measure the economic value of agricultural and industrial water use [10,[30][31][32][33][34][35][36][37], while fewer discussions have been conducted on domestic (public) water sectors as well as urban ecological water sector [38,39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The serious water crisis in northern China prompted the implementation of the South-to-North Water Diversion Project. The Middle Route of this project has been operational since 2008 and is providing freshwater to some large cities in northern China (Gao & Yu, 2018). However, this project is highly susceptible to water pollution, as pointed out by Lei, Zheng, Shang, and Wang (2018).…”
Section: Water Resources Research To Support a Sustainable Chinamentioning
confidence: 99%